RECONCEPTUALIZING RECORDS, THE ARCHIVE AND ARCHIVAL ROLES AND REQUIREMENTS IN A NETWORKED SOCIETY - GILLILAND, ANNE J. (Knygotyra, 2014)
Records created through institutional and personal activity are the primary concern of archives, regardless of the form or media of those records. This paper focuses on the implications of the networked society for how such records are created, as well as how they are defined and appraised by archivists, and the kinds of searching and uses to which they might be subjected. It argues that in responding to these implications, archives will have to move beyond the custodial and institutional mindset that has dominated the field for centuries and instead embrace a network orientation. It proposes and provides examples of several potential conceptualizations of “networked records”: the multi-provenance bureaucratic record and the record created by the crowd; the metadata record; the extra-institutional record, the transinstitutional and the transjurisdictional record, and the mobile or itinerant record; the stitched-together record; the mined, mapped and compiled record; and the implied or inferred record. The paper also identifies several dissemination and access challenges faced by archivists when networked records and their metadata accumulate into a virtual “archival corpus”. These challenges include the ways in which that corpus might be mined, forensically analyzed, cross-compiled, found lacking, augmented and otherwise searched or mapped to the benefit or detriment of organizational, scholarly, community and personal interests. After identifying a set of human rather than asset, data or task-centred principles that it is argued should inform archival activities such as appraisal, description and dissemination, the paper concludes that traditional appraisal techniques alone are unable to cope with these challenges. Instead the field working together with researchers in information retrieval (IR) should focus on innovating in the area of archival information storage and retrieval (“archival IR”) in ways that can exploit the networked creation and uses of records and other forms of primary data and their metadata, and respond to and protect against potential vulnerabilities, particularly those relating to privacy and security, that might be exposed by such developments.